Financial Management and Accounting Practices of Gayo Coffee MSMEs in Supporting Sustainable Tourism in Aceh, Indonesia - Admita; Jamaludin; Reza Imani Syawal; Bayu Anggara Sajangbati; Dini Murniaty (International Journal of Travel, Hospitality and Events, 2026)
ABSTRACT Purpose: This research aims to explore how financial management practices and accounting strategies implemented by Gayo Coffee MSMEs in Aceh, Indonesia, contribute to the sustainability of tourism-based local economies. Gayo Coffee, globally recognized for its distinctive flavor and organic cultivation methods, has become a central pillar in Aceh’s economic and tourism development. Research Methods: This study adopts a descriptive qualitative approach utilizing secondary data from the Central Bureau of Statistics (BPS), Bank Indonesia (BI), the Ministry of Tourism and Creative Economy (Kemenparekraf), and academic publications. Data were analyzed using thematic analysis and triangulation to ensure validity and reliability. Results and Discussion: Findings reveal that most MSMEs practice traditional but adaptive financial management through manual bookkeeping and cooperative-based funding. However, digital transformation has improved financial transparency through QRIS and e-wallet use. Despite progress, accounting literacy and standardization remain limited. Implication: The study emphasizes the importance of enhancing financial education, digital literacy, and accounting standardization to strengthen the role of MSMEs in sustainable tourism development. Keywords: financial management, accounting practices, MSMEs, Gayo coffee, sustainable tourism